Genome-Wide Identification of Destruxin A-Responsive Immunity-Related MicroRNAs in Diamondback Moth, Plutella xylostella - Shakeel, Muhammad; Xu, Xiaoxia; Xu, Jin; Li, Shuzhong; Yu, Jialin; Zhou, Xianqiang; Xu, Xiaojing; Hu, Qiongbo; Yu, Xiaoqiang; Jin, Fengliang (Frontiers in Immunology, 2018)
Plutella xylostella, a global key pest, is one of the major lepidopteran pests of cruciferous vegetables owing to its strong ability of resistance development to a wide range of insecticides. Destruxin A, a mycotoxin of the entomopathogenic fungus, Metarhizium anisopliae, has broad-spectrum insecticidal effects and has been used as an alternative control strategy to reduce harmful effects of insecticides. However, miRNA-regulated reactions against destruxin A have not been elucidated yet. Therefore, here, to identify immunity-related miRNAs, we constructed four small RNA libraries from destruxin A injected larvae of P. xylostella at three different time courses (2 h, 4 h, and 6 h) with a control, and sequenced by Illumina. Our results showed that totally 187 known and 44 novel miRNAs were identified in four libraries by bioinformatic analysis. Interestingly, among differentially expressed known miRNAs, some conserved miRNAs such as miR-263, miR-279, miR-306, miR-2a, and miR-308, predicted to be involved in regulating immunity-related genes, were also identified. Worthy to mention, miR-306 and miR-279 were also listed as common abundantly expressed miRNA in all treatments. The KEGG pathway analysis also indicated that differentially expressed miRNAs were involved in several immunity-related signaling pathways, including Toll signaling pathway, IMD signaling pathway, JAK-STAT signaling pathway, and cell adhesion molecules signaling pathway. To the best of our knowledge, this is the first comprehensive report of destruxin A-responsive immunity-related miRNAs in P. xylostella. Our findings will improve in understanding the role of destruxin A-responsive miRNAs in the host immune system and would be useful to develop biological control strategies for controlling P. xylostella.